Endothelial dysfunction in patients with myocardial ischemia or infarction and nonobstructive coronary arteries. Issue 4 (9th August 2020) - Simsek, Ersin Cagri; Sari, Cenk; Kucukokur, Murat; Ekmekci, Cenk; Colak, Ayfer; Ozdogan, Oner
Abstract: Purpose: The syndromes of myocardial infarction/myocardial ischemia with No Obstructive Coronary Artery Disease (MINOCA/INOCA) are seen more and more often. Endothelial dysfunction (ED) leading to ischemic events has been reported in many of these patients. We aimed to compare patients with MINOCA and INOCA regarding brachial artery flow‐mediated endothelium‐dependent vasodilation (flow‐mediated dilation [FMD]) and plasma concentration of cardiotrophin‐1 (CT‐1). Methods: We included 42 patients with MINOCA and 38 patients with INOCA. Endothelial function was assessed by measuring FMD% and nitroglycerin‐mediated dilatation (NMD%) in the brachial artery. The plasma level of CT‐1 was determined by solid‐phase enzyme‐linked immunosorbent assay. Results: FMD% was significantly lower in MINOCA than in INOCA patients (6.45 ± 2.65 vs 8.94 ± 3.32, P < .001), without significant difference in NMD% (10.69 ± 3.19 vs 12.16 ± 3.69, P = .06). Plasma CT‐1 levels were not significantly different: 40.1 pg/mL (22.5‐102.1) vs 37.2 pg/mL (23.5‐67.2), P = .53. Conclusion: Our results suggest worse ED in MINOCA than in INOCA patients, but demonstrated no difference in CT‐1 levels between patients with stable and unstable ischemic heart disease and normal coronary arteries.